Effect of Implementing Family-centered Empowerment Model on the Quality of Life in School-age Children Diagnosed with Rheumatoid Arthritis - Nahid Pilevar; Monir Ramezani; Abdolreza Malek; Hamidreza Behnam Vashani (Mashhad University of Medical Sciences, 2019)
Background: Rheumatoid arthritis is the most prevalent chronic rheumatologic disease of children. The quality of life (QOL) in these individuals is affected by physical pain, discomfort, treatment complications, and frequent absences from school leading to academic failure. No research similar to the present investigation was performed in this area. Aim: We aimed to evaluate the problems of children with rheumatoid arthritis. Moreover, we assessed the effect of family-centered empowerment on the QOL of these children. Method: This randomized clinical trial was performed on 60 children aged 8-12 years diagnosed with rheumatoid arthritis in Akbar Pediatrics Hospital, Mashhad, Iran in 2018. The subjects were divided into test and control groups. The four stages of family-centered empowerment model, namely improvement of knowledge, self-efficacy, self-esteem, and assessment were executed for the test group. After a month, the inventory of pediatric quality of life was completed again. Data analysis was performed by Mann-Whitney U test, independent t-test, and paired t-test using SPSS version 16. Results: No significant difference was observed between the groups regarding age (P=0.351). In addition, the post-intervention QOL of the test group was significantly higher than the control group (P=0.004). There was a significant difference between the pre- and post-intervention QOL in the test group (P < 0.001). Implications for Practice: This study indicated the effect of family-centered empowerment model on the physical, emotional, educational, and social dimensions of QOL of children aged 8-12 years diagnosed with rheumatoid arthritis. As a result, this model is recommended to empower the children with this disease or other chronic diseases and their caregivers.